MENINGKATKAN AKTIVITAS DAN KETERAMPILAN KERJA SAMA SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL), VISUAL AUDITORY KINESTETIK (VAK), DAN TALKING STICK PADA MUATAN IPAS SEKOLAH DASAR: Penelitian Tindakan Kelas - Daniela Irena Rumintang Simangunsong; Ratna Purwanti (STKIP Subang, 2024)
The problems in the research focus on low student understanding, limited learning experience, lack of student cooperation, and lack of interest in learning science content in class IV SDN Belitung Utara 1. These problems are caused by a one-way learning approach, lack of use of models. learning that encourages the development of students' collaboration skills, as well as a lack of variety in the presentation of material which results in less interesting and enjoyable learning. Efforts to solve this problem are conducted utilize Problem Based Learning (PBL), Visual Auditory Kinesthetic (VAK), then Talking Stick models. The aim of this look for is to upgrade student activity, collaboration skills, and their learning outcomes. This research used the Classroom Action Research (PTK) method which was carried out in four meetings. Data was collected through observing activities by teachers and students and student collaboration skills, which were then analyzed using descriptive analysis and cross tabulation techniques to produce tables, figures and interpretations based on percentages.According to the research findings, instructor activity increased from a score of 25 at the first meeting to a score of 35 at the fourth. Student activity also increased significantly from 17% at the initial meeting to 94%, with the criteria being very active. Students' collaboration skills increased from 28% to 100% over four meetings, with very skilled criteria. The criteria for achieving student learning objectives also increased from 22% to 94%. It is possible to draw the conclusion that the application of the model Problem Based Learning (PBL), Visual Auditory Kinesthetic (VAK), then Talking Stick effective in increasing student activity, collaboration skills, and their learning outcomes in science learning in class IV at SDN Belitung Utara 1.